Alternative Use of Space as A Self-Organizing Solution by Local Society to Meet Shortage of Living Spaces in The Informal Settlements of Egypt - El-Akhdar, Ammar; Kenway, Emad; M. Osman, Tarek; Abdrabo, Karim I.; Salem, Muhammad (Journal of Social Transformation and Regional Development, 2023)
This research seeks to identify the land use dynamic phenomenon in the unplanned settlements in Greater Cairo Metropolitan region (GMCR) which embodied in the alternative use of space (AUS). This phenomenon represents the way for the poor communities to meet their needs of space for living, working, and entertainment purposes for free or for low costs. It is considered the first research which included clarification for this phenomenon although the main role of AUS to meet the poor communities needs of lands in GCMR. By field survey and direct interviews with users and surrounding residents we have identified AUS types, times of use and Frequency for each type in addition to impacts of it on the prices of essential needs. Based on the goals of urban sustainability we have identified positive and negative aspects of AUS on our case study district. AUS provide lands for various needs of essential activities in free or low-cost rent which reduced the price of essential needs to 13 times for some item’s comparison with the nearest planned district. AUS reduce living expenses and help low-income families and offer cheap choices of housing, goods, transportations, essential services, entertainments, in addition to work opportunities. We can consider the AUS as a tool for achieving sustainable development in the poor communities by efficient use of resources and providing job opportunities within the community.